Towards risk-informed design and operation of ammonia-powered ships: Critical aspects and prospective solutions - Rustam Abubakirov; Ming Yang; Giordano Emrys Scarponi; Valeria Casson Moreno; Genserik Reniers (Ocean Engineering, 2024)

Metallogeny of Late Paleozoic lode gold mineralization of western Tien Shan: From orogenic shortening to intracontinental strike-slip shearing - Xiaobo Zhao; Chunji Xue; Reimar Seltmann; Weice Zhao; Guoxiong Ma; Bakhtiar Nurtaev; Rustam Mirkamalov; Nikolay Pak (Earth-Science Reviews, 2024)

Bison sex matters: the potential of proteomic tooth enamel analysis for determination of ancient human subsistence strategies - Natalia Berezina; Rustam Ziganshin; Ksenia Kolobova; Anastasia Koliasnikova; Stanislav Medvedev; William Rendu; Alexandra Buzhilova (Archaeological and Anthropological Sciences, 2024)

Anti-inflammatory activity of the phenol rich fraction of Garcinia pedunculata Roxb (ex. Buch Ham): an in vitro and in vivo study - Kasturi Dutta; Akalesh Kumar Verma; Munmi Gogoi; Mary Devi; Maishnam Rustam Singh; Namram Sushindrajit Singh (Inflammopharmacology, 2024)

Role of Cryoconite Translocation on the Biogeochemical Features of Alpine Soils at the Central Caucasus Region, Mount Elbrus - Ivan Kushnov; Rustam Tembotov; Timur Nizamutdinov; Evgeny Abakumov (Environmental Processes, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Spatio-temporal variation in progression rates of black band disease between Pramuka Island and Pari Island of the Seribu Islands, Indonesia - Ofri Johan Ofri; Rendy Ginanjar; Agustin Rustam; Idil Ardi; Lili Sholichah; Rita Rachmawati; Rikoh Manogar Siringoringo; Muhammad Abrar; Ni Wayan Purnama Sari; Giyanto; Andrias Steward Samusamu; Nani Ingrid Undap; et al. (Frontiers in Marine Science, 2024)
Black band disease (BBD) is one of the oldest recognized diseases of scleractinian corals. This disease is little known on the variation of progression rates across relatively small spatial scales and how local variations in the environment can impact prevalence and spread. The purpose of this study was to explore the progression of BBD on genus Montipora in relation to spatio-temporal environmental parameters in two islands of the Seribu Islands, North Jakarta, Indonesia during dry season and rainy season. Monthly underwater pictures were taken for determining the progress of disease level. Interestingly, the progression rate of the disease recorded at Pramuka Island was higher (8.10 cm 2 day -1 ) than the one at Pari Island (3.79 cm 2 day -1 ). In Pramuka Island, the infected corals had almost 89% of the dead surface, compared to only 68% at Pari Island. Similar to other studies in the region, we confirmed that the disease progressed faster during the dry season, where the environmental parameters, such as temperature, light intensity, and phosphate, were starting to increase, while total organic matter, current flow rates, and turbidity were lower. Progression of the disease was significantly different between seasons ( p <0.001), but not between sites ( p =0.118). Therefore, the progress of BBD has a higher impact at the more populated Pramuka island than at the less populated Pari Island, in addition to the influence of environmental parameters on coral vulnerability to diseases.

Multiculturalism and interculturalism managing diversity in cross-cultural environment Multiculturalism and interculturalism managing diversity in cross-cultural environment , Edited by Muhammad Mohiuddin, Md. Tareque Aziz and Sreenivasan Jayashree, London, United Kingdom, IntechOpen, 2023, 236 pp., €140,40 (hardcover), ISBN 9781837681440 - Rustam Rustam; Hendra Sulistiawan; Haris Firmansyah (The Social Science Journal, 2024)

Impact of climate change on food security in the Central Asian countries - Fang Su; Yu Liu; Lvfan Chen; Rustam Orozbaev; Liangcheng Tan (Science China Earth Sciences, 2024)